Non-Observance Of Grice’s Maxims Found In “The Grapevine: Gossip At Work, What Should You Do As A Leader?” Drama Series Script Produced By The Calvin Company - Amma Safina Saradifa (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
Misunderstanding and misinterpreting are the main problems in communication. These phenomena are also called as non-observance maxim because the speakers to observe cooperative principle in a conversation. There are four types of maxim in cooperative principle; maxim of quality, maxim of manner, maxim of relation, and maxim of manner. Meanwhile, the various of non-observance maxim is divided into flouting a maxim, violating a maxim, infringing a maxim, opting out a maxim, and suspending a maxim. This study intends to analyze and describe the types of non-observance maxims, the speaker’s intention, and the variation of maxims found in “the Grapevine: Gossip at Work, What Should You Do as A Leader?” drama script series produced by the Calvin company based on Grice’s theory. For this purpose: a descriptive qualitative study was used where the subject is the participants or characters in the drama series. While the object of this study is the types of non-observance maxims, the speaker’s intention, and the variation of maxims. The data were collected by using video observation. The video is taken from the youtube of teamwork and leadership channel. The data analysis was done by (1) eliciting the video from the youtube channel, (2) observing the data by watching and listening the drama series, (3) writing down the script, (4) analyzing the types of non observance maxims by marking and noting all the dialogue used by the characters, (5) categorizing all the data of non-observance maxims, and (6) making a conclusion for this study. The findings show that floating and violating a maxim of quality and quantity are the most types of non-observance maxims found in the drama series. In addition, these phenomenon used by the female workers in the drama series to express their feelings in dealing with an issue or rumor happened in their company. They are also used by the head of accounting in the company to give more information, explanations, and clarifications to the female workers about the issue. Keywords: Cooperative principle, non-observance maxim, implicature